2017
DOI: 10.1002/hed.24869
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of surgical approach for advanced oropharyngeal and hypopharyngeal cancer: A retrospective analysis

Abstract: We recommend that surgery be considered a first-line treatment for advanced oropharyngeal and hypopharyngeal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(73 reference statements)
0
8
0
Order By: Relevance
“… 2 However, recent evidence confirms that patients who undergo primary surgery have better survival outcomes than those treated with non-surgical strategies, which indicates that surgery remains the primary option for this disease. 13 16 Because of the rich lymphatic network in the neck and the submucosal invasive behavior of tumor cells, the recurrence rates for patients with HSCC who are treated with surgery are relatively high. 5 Thus, POAT including RT, chemotherapy, and immunotherapy could also be useful to eliminate residual cancer cells and reduce disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, recent evidence confirms that patients who undergo primary surgery have better survival outcomes than those treated with non-surgical strategies, which indicates that surgery remains the primary option for this disease. 13 16 Because of the rich lymphatic network in the neck and the submucosal invasive behavior of tumor cells, the recurrence rates for patients with HSCC who are treated with surgery are relatively high. 5 Thus, POAT including RT, chemotherapy, and immunotherapy could also be useful to eliminate residual cancer cells and reduce disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies insisted that (chemo)radiotherapy for T4a hypopharyngeal cancer showed a poor survival rate compared to surgery . On the other hand, a multi‐institutional study which performed a matched‐pair analysis between surgery and chemoradiotherapy between 2006 and 2008 showed no significant differences in survival or local control rates between the two treatment groups even in T4a category patients …”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment for locally advanced hypopharyngeal cancer is controversial, especially in T4a cancer. For T4a hypopharyngeal cancer, (chemo)radiotherapy showed a poor survival rate compared to the radical surgery, and the invasion of thyroid or cricoid cartilage were considered as to be difficult to preserve laryngopharyngeal function after chemoradiotherapy . Therefore, surgery is considered as the treatment of choice for T4a cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the Western countries, clinicians tend to choose less expensive conservative treatment (radiotherapy and chemotherapy) due to its low incidence [ 1 ], while in China, HSCC patients typically receive comprehensive treatment with surgery [ 2 ]. A variety of surgical skills and principles have been developed, resulting in significant improvement for laryngeal function and swallowing function [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%